Development and evaluation of a convective type dryer for nutmeg mace (Myristica fragrans houtt) - CHIKKANNA G.S; Er. Prince M.V (Guide) (Tavanur 2008 Department of Post-Harvest Technology and Agricultural Processing)
Development and evaluation of a convective type dryer for nutmeg mace (Myristica fragrans houtt)
Development and evaluation of a convective type dryer for nutmeg mace (Myristica fragrans houtt)